TELA’AH PEMIKIRAN ALWI SHIHAB TENTANG TOLERANSI BERAGAMA DALAM BUKU ISLAM INKLUSIF - Nopriansyah, Eko (Nurani, 2017)
This research is titled Tela'ah Thought Alwi Shihab on Religious Tolerance in the Book of Inclusive Islam. This study aims to examine the various thoughts of Alwi Shihab in his book Islam Inclusive. To know the various problems that background the happening of intolerant cadet in religion in the middle of Plurality and religious diversity. To know how Alwi Shihab explains the various solutions and thoughts that he poured in his book Islam Inclusive. In today's reality we often find that the various conflicts between religious communities in various majorities and minorities of Muslims have become viral in the Netizen world about the persecution of the Rohingya Muslim community. In Miyanmar, this is certainly a test of every Religion that echoes religious tolerance. However, by re-examining the thoughts of Alwi Shihab became an important learning for every religious people. In an Inclusive Islam book written by Alwi Shihab, a scholar from the University of Temple of America and a Doctoral Degree at Egypt's Ayn Syam University, has made a significant contribution in establishing a religious tolerance stance, addressing issues and resolving conflicts and relationships between religious communities with views the more Universal. In examining the various thoughts of Alwi Shihab and by conducting literature study the authors found various thoughts of Islamic thought that supports the concept of religious tolerance in the offer Alwi shihab so that Alwi shihab thought this becomes something important contribution, especially in build attitude of religious tolerance. More to build tolerance in a group of religions who have different views to embody and revive the Islamic substance as Rahmatallil Alamin.